Save the Last for the Best: The Halo Effect and the Impact of Last Experience on Judgment - Anggreni, Ni Wayan Yuli (CV. Publikasi Indonesia, 2025)
Early adulthood is a developmental stage characterized by increased autonomy, where individuals actively make independent decisions and explore various choices to gain experience. College students, as part of this stage, often utilize opportunities to evaluate products and experiences that may shape their preferences and judgments. One psychological phenomenon related to decision-making is the end experience effect, which suggests that the final part of an experience can disproportionately influence overall evaluations, potentially leading to a positivity bias. This study aimed to examine the effect of end experience on individual assessments of chocolate consumption among college students, specifically investigating whether end experience influences positivity bias. The hypothesis proposed that participants exposed to a more positive end experience would demonstrate higher positivity bias in their evaluations. The study employed an experimental posttest-only design with nonequivalent groups, consisting of an experimental group and a control group. A total of 24 participants (12 male and 12 female), aged 19–24 years, were involved in the study. Data were analyzed using an independent samples t-test to compare the assessment outcomes between groups. The results indicated that there was no significant effect of end experience on positivity bias among students (t = −0.801, p = 0.432). These findings suggest that, within this context, end experience alone may not be sufficient to shape evaluative bias in early adulthood. The study contributes to the understanding of decision-making processes and highlights the need for further research with larger samples and varied stimuli to better capture the complexity of experience-based evaluations.